2014
DOI: 10.3109/17518423.2014.916761
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions in preschool children with cerebral palsy – Assessment and early intervention – A pilot study

Abstract: The children in our sample showed age-appropriate levels of executive functions before attending PIH. Some aspects of executive skills difficulties were reduced after PIH. Using BRIEF-P contributed to the differentiation of cognitive strengths and weaknesses among the children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Future studies following up children with CP as they enter adolescence and adulthood will also be valuable, to further understand the impact of challenges in these areas across the lifespan. This is particularly important as previous studies, including in the population of individuals with CP (Stadskleiv et al, 2016), indicate that executive functions continue to develop throughout adolescence and into early adulthood (Sørensen et al, 2016). As such, more subtle difficulties may become apparent later in a child's developmental trajectory, as environmental demands and expectations increase.…”
Section: Limitations and Future Researchmentioning
confidence: 97%
See 2 more Smart Citations
“…Future studies following up children with CP as they enter adolescence and adulthood will also be valuable, to further understand the impact of challenges in these areas across the lifespan. This is particularly important as previous studies, including in the population of individuals with CP (Stadskleiv et al, 2016), indicate that executive functions continue to develop throughout adolescence and into early adulthood (Sørensen et al, 2016). As such, more subtle difficulties may become apparent later in a child's developmental trajectory, as environmental demands and expectations increase.…”
Section: Limitations and Future Researchmentioning
confidence: 97%
“…Executive functioning (EF) refers to higher order cognitive abilities and processes associated with deciding on, planning and working towards goals (Piovesana et al, 2015;Warschausky et al, 2017), regulating emotions and behaviour (Diamond, 2013), and responding flexibly in the face of changing situations or difficulties (Sørensen et al, 2016). As executive functioning skills are key in all parts of daily life, including health, academic and vocational achievement (Diamond, 2013), participation (Bottcher et al, 2010), and adaptive functioning (Warschausky et al, 2017), impact of impaired EF can be wide-ranging.…”
Section: Executive Functioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that children with CP have increased risk for deficits in sustained attention (Bottcher et al, 2010;Lemay et al, 2012;Mak et al, 2018), working memory (Goble et al, 2012;Stadskleiv et al, 2018;Van Rooijen et al, 2014, visuospatial abilities, and executive functioning (Sørensen et al, 2016;Whittingham et al, 2014). Cognitive impairments are associated with deficits in motor function (Hoare et al, 2018;Warschausky et al, 2017).…”
Section: Interactions Between Movement Impairments and Impairments In...mentioning
confidence: 99%
“…The higher risk and incidence of CP in SA may be attributable to the prevalence of human immunodeficiency virus (HIV) and acquired immunodeficiency syndrome (AIDS), malaria, poverty-related malnutrition, tuberculosis (TB) and meningitis observed in some provinces, such as Limpopo (Treasury.gov.za 2019 ). Children living with HIV and AIDS may present with neurological impairments caused by the virus, resulting in complications, such as HIV encephalopathy (HIVE) and HIV-associated neurocognitive disorders (HAND) causing injury to the developing brain (Croucher & Winston 2013 ; Levin 2006 ; Sørensen Kristian et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%